Influence of humic acids on zinc oxide nanoparticles and zinc chloride toxicity to Enchytraeus crypticus studied in agar-based exposure media - Hrdá, Kateřina; Konopáčová, Eliška; Vrzáčková, Inka; Pouzar, Miloslav (University of Pardubice, 2018)
Composition of the exposure media always affects the properties of nanomaterials. In terrestrial ecotoxicology, the complex nature of the soil highly complicates the prediction of impacts of pollutants upon the environment. In our study, less complex agar-based exposure medium had been therefore used instead a soil. An acute toxicity of zinc oxide nanoparticle (ZnO-NPs, mean particle size diameter of 10 nm) powder and of water-soluble salt of zinc (ZnCl2) to annelid Enchytraeus crypticus were tested, while agar-based exposure medium was modified with two sources of humic acids (sodium humate, peat) in order to study the influence of soil component and its form on toxicity of zinc. In the case of ZnCl2, an addition of humic acid always reduced the toxicity. The respective values of LC50 were 13.2, 28.8, and 191 mg kg–1 for pure agar, agar with sodium humate, and agar with peat, respectively. On the contrary, the addition of sodium humate into an agar increased toxicity of ZnO NPs and the reduction in toxicity was observed only for the addition of a peat. The corresponding LC50 values then were 43.5 (pure agar), 15.8 (agar with sodium humate), and 304 (agar with peat) mg kg–1.
Keywords: terrestrial ecotoxicity test; agar; potworm; Enchytraeus crypticus; humic acids; peat